Gellan gum-liI gel polymer electrolytes - Halim, N.F.A.; Majid, Siti Rohana; Arof, Abdul Kariem; Kajzar, F.; Pawlicka, A. (Taylor & Francis, 2012)
Gellan-based polymer electrolytes (PEs), doped with lithium iodide (LiI), were prepared and their electrical properties were characterized. The samples are thermally stable up to 234 degrees C and exhibit ionic conductivity of 3.8 x 10(-4) S/cm at room temperature for the sample doped with 40 wt% of LiI. Addition of 10 wt% of glycerol promotes an increase of the ionic conductivity to 1.5 x 10(-3) S/cm, which remains stable up to 100 degrees C. The activation energies of 2.4 to 12.4 kJ/mol were derived from the Arrhenius model. The repeated ionic conductivity measurements as a function of temperature show that these membranes can be reversibly used between the room temperature and 100 degrees C.